Development of a low cost cook-off test for assessing the hazard of explosives - Frota, Octavia (Cranfield University, 2015)
A low cost Cook-Off experimental facility has been established to provide a convenient method of ranking explosives in their response to Cook-Off by the time to event under two widely different heating rates and at two different scales. This thesis describes the literature review undertaken as preparation for the purposed study and all the experimental work developed comprising the design of the trials vehicles, the demonstration of their suitability for Fast and Slow Cook-Off trials with confined explosive systems, the preparation of the samples and test vehicles to be trialled as well as the set-up of adequate facilities to undertake the scheduled firing programme. Results are reported for Cook-Off tests on TNT, RDX, and their mixtures. The emphasis of the study is on time to event, and temperature at event, and in addition a qualitative assessment of the violence of the event was made by examination of the fragments of the vehicles, although it is accepted that the relatively light and low cost design of the vehicle may lead to variable confinement in the early stages of the explosive event, and hence to a wider spread of responses than would be obtained from a more heavily confined and more costly vehicle. The test vehicles give results, which differentiate between the various explosives and explosive mixtures trialled and between the scales. More experiments are required to establish the reproducibility of the measurements. The design of the equipment makes this a relatively inexpensive undertaking. The experiment was modelled using published kinetic data, but the calculated time to event differed from that observed to different extents at the two scales. It is hypothesised that the mechanism may change over the prolonged heat soaks and that quantitative scaling is not possible with the available information. Further work is also suggested using a different type of Cook-Off test vehicle, which will in our opinion reduce even further the cost of Cook-Off testing, due to reduction in man-hours of preparation involved and manufacture cost of the Cook-Off test vehicles, and consequently of ranking of explosives.
Keywords: Cook-off - Explosives; Energetic materials; Explosives